The Marketing Mix Factors that Influence to Selection of Bank Loan Service of Private Staffs in Bangkok - NA NAKORN, Nattanicha (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The objectives of this research include 1) To study the choosing bank loan service of private employees in Bangkok when classifies by personal factors and 2) The influence of marketing mix factors that is affected the selection of bank loan service of private employees in Bangkok. In addition, a researcher collected data from a sample of 400 cases by using convenient random sampling. The statistics used for data analysis consisted of frequency, percentage, average, standard deviation, T value analysis, one-way analysis of variance and multiple regression analysis. The result of this study indicated that 1) Selection of bank loan service of private staffs in Bangkok as classified by the personal factors, there are statistically significant differences and to categorized by education level and income. 2) The factors of the marketing mix that affects the selection of bank loan service of private employees in Bangkok which includes the product (b=0.11), price (b=0.28), distribution channel (b=0.21) and marketing promotion (b=0.10). Besides that, the equation has a predictive power equal to 35; and it can write the equation as follows Y = 0.11X1* +0.28X2** +0.21X3** +0.10X4* Article history : Received 22 December 2019 Revised 4 February 2020 Accepted 9 February 2020 SIMILARITY INDEX = 0.00 %